The Plasticity of Some Fittable Surfaces on a Given Quadruple of Points in the Three-Dimensional Euclidean Space - Zachos, A.N. (Журнал математической физики, анализа, геометрии, 2014)
We construct a two-dimensional sphere in the three-dimensional Euclidean space which intersects a circular cylinder in three given points and the corresponding weighted Fermat-Torricelli point for a geodesic triangle such that these three points and the corresponding weighted Fermat- Torricelli point remain the same on the sphere for a different triad of weights which correspond to the vertices on the surface of the sphere. We derive a circular cone which passes from the same points that a circular cylinder passes. By applying the inverse weighted Fermat-Torricelli problem for different weights, we obtain the plasticity equations which provide the new weights of the weighted Fermat-Torricelli point for fixed geodesic triangles on the surface of a fittable sphere and a fittable circular cone with respect to the given quadruple of points on a circular cylinder, which inherits the curvature of the corresponding fittable surfaces.